Virtualization of customer equipment: Challenges and opportunities. Issue 6 (10th June 2020) - Meneses, Flávio; Corujo, Daniel; Aguiar, Rui L.
Abstract : Emerging concepts such as Software Defined Networking (SDN), Network Function Virtualization (NFV) and Network Slicing have been pushing new and flexible ways for providers to manage their services through the simplification of the hardware, allowing a faster deployment of new services and the optimization of their capital and operational expenses. Accordingly, the customer premises equipment (CPE) used at the customer site for his/her access to the network has been changing its paradigm in order to allow both customers and providers to benefit from virtualization. In this paper we review the latest developments and proposals on the CPE virtualization, discussing its challenges and opportunities, as well as point out for future directions.